Dual information processing of cardiovascular disease risk perception : an examination of the Extended Parallel Process Model - Moylett, Sinéad (Trinity College (Dublin, Ireland). School of Psychology, 2017)
The overall objective of this thesis was to examine dual information processing of CVD risk communications through empirical manipulations of both information processing modes (cognitive and affective), and to examine the effect of such on risk appraisals for CVD and efficacy appraisals for the associated health behaviours. The thesis evolved into an examination of the Extended Parallel Process Model (EPPM; Witte, 1992, 1994) for communicating about CVD among Irish samples. Chapter 2 presented a narrative review of the most relevant literature from dual processing theories of risk and decision-making. One of the main outcomes of the review was the lack of consideration given to the role of affect, and few previous investigations could be identified that have given equal consideration to both affective and cognitive processes in dual information processing of health communications. In trying to better understand the exact processes of “how” both information processing modes influence threat and efficacy appraisals for health threats and their associated health behaviours, no previous research has assessed both incidental and integral manipulations of information processing for CVD. In line with this, it was noted that there was a lack of research examining CVD in comparisons to other diseases (e.g., cancer). Chapter 3 presents the method and results of an equal examination of dual information processing for CVD risks and the associated health behaviours within health communications, utilising an incidental manipulation. The study utilised a novel combination of images and word search puzzles to prime both affective and cognitive information processing modes, and to examine the potential impact of such on CVD risk perception. The results of the study did not support the manipulation. Additional statistical analyses (e.g., EFA) were conducted and suggested a slight theoretical shift for future studies, with more of a focus on integral information processing for health communications. Initially, chapter 4 presented a review of the EPPM for CVD and the associated health behaviours. The objective of study 2 was an experimental test of EPPM-based communications about CVD and the associated health behaviours. Given the lack of overall effects from the EPPM-based CVD messages and the inconsistent results for threat, study 2 provided little evidence to support the use of the EPPM. However, the study suffered from heavily skewed data and sampled a young population. Future investigations aimed to conduct a more focused examination of EPPM-based CVD risk messages among an older population (60+ years). Chapters 5 and 6 discussed the mixed method approach of study 3. Chapter 5 presented a quantitative examination of six EPPM-based threat-to-efficacy ratios in CVD health messages. Part 1 of study 3 provided little evidence to support the use of the EPPM among older individuals. Due to these results, a think aloud methodology was used in part 2 to allow for a more in-depth investigation (Chapter 6). The qualitative findings highlighted a few important considerations; varying levels of threat appraisals for different CVD manifestations and the considerable role of comparative perceptions were found to impact on the effectiveness of the current EPPM-based CVD risk communications. Chapter 7 is a discussion of the results and findings from all three studies. Overall, there was a lack of evidence found to support the EPPM, suggesting that the theory might not be the most suitable model for developing CVD risk communications. A number of key findings should be noted: the considerable role of comparative examples for threat and efficacy appraisals, misleading levels of health literacy, and varying threat perceptions for different CVD manifestations.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin